'Wondering and waiting' after obstetrical brachial plexus injury: Are we underestimating the effects of the traumatic experience on the families?. Issue 3 (August 2014) - Dematteo, Carol; Bain, James R; Gjertsen, Deborah; Harper, Jessica A
Background: Obstetrical brachial plexus injury (OBPI) in children can cause great distress to a family due to uncertain recovery, variability in spontaneous recovery and unclear indicators for surgery. Objective: To investigate the impact of having a child with OBPI on the family and whether the Impact on Family Scale (IoFS) can assist in addressing family concerns. Methods: A mixed-method (cross-sectional survey and semistructured interviews) study design was used. Results: Thirty-eight families of children with OBPI completed the IoFS. Surgery significantly predicted a higher IoFS total impact score (P=0.02). No statistically significant association between the total impact score and severity or age was found, suggesting that impact on family was not dependent on these factors. Themes that emerged from the interviews included traumatic birthing experience, wondering and waiting, and experiencing surgery. Conclusion: All families should receive support and acknowledgement of the widespread impact of OBPI.